Redimensionar o corpo: biologicidade, racionalidade e poder em contextos de formação - De Sa, Jonivan Martins (2022)
The following thesis starts from a possible resizing of the role of the body in the more general processes of teaching/learning, or formation. The work starts from the meaning of their bodies, as well as context to historical dates, with two instances, in the sense of (1) power relations, as (2) the question of knowledge, processes of reflection are considered as essential elements of the point from the point of view of a reflection on which these bodies are defined. Some works, the work aims to explore, but precisely, as initially by Nietzsche and Foucault. Nietzsche in the comprehensive processes from the body – links, gives, the advent of rationality to instances; while Foucault inserts the reality of power in this rationality/body axis. Notions such as biopolitics and device are explored in this perspective, in which power defines bodies, directing their material and subjective production. Still exploring our understanding as relationships between the body, the research articulates the rational search and the knowledge coming from education and neurobiology, which corroborate in the sense of the need for a systematic reflection about the role that the body, or organism, has as a constituent factor of training processes. As a progressive brought by neurobiology, linked to neural plasticity and useful to which the interaction between the nervous system and the long training process throughout history are exploratory points, as well as a historical perspective of the training contexts and their capacity. Glimpse, therefore, is a research study that aims to think about the way of education as a culture and a neurobiology, relating them to the phenomenon of education. The graphic work, which constitutes a research of bibliographic knowledge from the perspective of a hermeneutics of the corporeal, also aims to contribute to the realization of transdisciplinary publications in the area of education, taking into account its social aspects and path. In the same way, power relations are established as constituents, as well as their behavioral actions that induce subject people.